Pengembangan pengetahuan sains melalui metode eksplorasi lingkungan sekitar anak - Suliani, Suliani (Jurnal Kajian Pendidikan IPA, 2025)
The Development of Science Knowledge Through Methods of the Environment’s Exploration Around Children. This study aims to describe the process of developing early childhood scientific knowledge through environmental exploration methods. The research subjects consisted of a classroom teacher and twelve children aged 5–6 years in Class B, comprising six boys and six girls. This study employed a qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data display, and drawing conclusions. The results indicate that the development of children's scientific knowledge was carried out in three main stages: (i) the teacher prepared the exploration activities by setting the objectives; (ii) the teacher implemented the activities by discussing the procedures, tools, and materials with the children, as well as guiding and supervising them throughout the process; and (iii) the teacher conducted evaluations and assessments of the children’s exploration outcomes. The study concludes that environmental exploration is an effective strategy for enhancing scientific understanding in early childhood.